Troponin level and its prognostic role in occurrence of MI - Kh Amouzadeh (Babol University of Medical Sciences, 2001)
Objective: Cardiac diseases, especially myocardial infarction (MI) are one of the major causes of mortality and cause heavy expenditure of money. Nowadays, investigations are done to prevent and control the risk factors, especially identification of prognostic factors that elevated levels of serum Ctpn-I is one of them. Methods: 100 patients with UA and diagnosis of CHF or P/E who had ischemic changes in their EKG with regard to occurrence of MI or cardiac death and serum Ctpn-I level were followed in a 6 week period. The incidence of MI and cardiac death in elevated Ctpn-I and normal groups were compared and analyzed statistically. Findings: From 100 selected patients, 24 cases had positive elevated level of serum Ctpn-I who 6 of them had MI or died and among 76 cases, only 3 of them had MI or died (RR=6.33). Conclusion: In this study, elevated of serum Ctpn-I, is an independent prognostic factor for occurrence of MI or cardiac death during 6 weeks.